THE ROLE OF PUBLIC HEALTH INITIATIVES IN REDUCING THE BURDEN OF COMMON SKIN DISEASES GLOBAL PERSPECTIVE ON ACNE, PSORIASIS, ECZEMA, AND SKIN CANCER (The Research of Medical Science Review, 2025)
Skin diseases are a serious challenge to the global health systems because of the higher incidences that result in complications and poor quality of life. Skin conditions such as psoriasis, eczema, acne vulgaris, and skin cancer have a substantial impact on patient care and medical expenses. These burdens have been well managed by public health interventions aimed at prevention, early detection, and better health access, especially in the developing world. SunSmart in Australia or the National Eczema Association in the United States are good examples of programs where specific disease incidence rates have been lowered and patients’ experiences improved by raising awareness and using community approaches. Still, there are some limitations in dermatological care in LMICs: shortage of resources and efforts, cultural taboos, and constrained health system construct. This review emphasizes the need for dermatology in primary healthcare services, increased awareness of three prevention strategies, and cultural factors. Concluding these gaps will speak great volumes as a step towards reducing the burden of skin diseases all over the world and ensuring equitable health for the affected population.